AF-CARE: The current approach in atrial fibrillation management - Rizal, Ardian (Universitas Brawijaya, 2025)
Despite improvements in treatment, atrial fibrillation (AF) continues to pose a serious threat to global health, with increasing rates of morbidity and mortality. By endorsing the AF-CARE approach, the 2024 ESC guidelines shift the paradigm from the conventional